2015
DOI: 10.2319/020714-97.1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in psychological traits between lingual and labial orthodontic patients: Perfectionism, body image, and the impact of dental esthetics

Abstract: This pilot study may indicate that lingual orthodontic patients are more perfectionists than labial orthodontic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…Our results revealed that females felt a higher psychosocial impact of dental aesthetics and aesthetic concern (AC) compared to males, and lower dental self-con dence (DSC). These results are in agreement with previous reports that observed less self-con dence in girls compared to boys [20,21]. Also in agreement, previous studies found higher dental concern and oral demands with females than males, who are more comfortable with their dental appearance [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that females felt a higher psychosocial impact of dental aesthetics and aesthetic concern (AC) compared to males, and lower dental self-con dence (DSC). These results are in agreement with previous reports that observed less self-con dence in girls compared to boys [20,21]. Also in agreement, previous studies found higher dental concern and oral demands with females than males, who are more comfortable with their dental appearance [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…In case of DSC, the results showed that females and participants with mothers' having university education expressed less positive DSC and high SI. These results are in agreement with previous reports that observed less self-con dence of girls compared to boys [27,28]. In contrast, Chen et al [26] found that males compared to females, showed more adverse aesthetic attitude and dental self-con dence when anterior teeth were missing, and higher improvement of the social impact, aesthetic atti tude and dental self-con dence after implantation [26].…”
Section: Discussionsupporting
confidence: 92%
“…A study by Jung ( 27 ) observed that the girls were generally less self-confident than the boys, in contrast to the present findings. A number of studies have examined the association between aesthetics and gender and have concluded that women are generally more demanding with regard to beauty and aesthetics, more affected by what they consider facial and corporal aesthetic defects and more critical in general regarding everything related to aesthetics ( 13 , 28 - 32 ). According to several studies ( 1 , 12 , 16 ), women present a greater psychosocial impact than men.…”
Section: Discussionmentioning
confidence: 99%